2008
DOI: 10.1136/tc.2007.024216
|View full text |Cite
|
Sign up to set email alerts
|

Does tobacco industry marketing excessively impact lesbian, gay and bisexual communities?

Abstract: LGB communities, especially lesbian and bisexual women, appear to be effectively targeted by tobacco industry marketing activities. Strategies to limit tobacco industry marketing, and increase individuals' resistance to marketing, may be critical to reducing smoking among LGB populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
110
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 22 publications
2
110
0
Order By: Relevance
“…Research has found that students who attended schools with more supportive environment for sexual minorities were significantly less likely to report substance use and emotional distress (Heck et al, 2011(Heck et al, , 2014Konishi et al, 2013). Independent research also note that tobacco industry has historically targeted sexual minority populations (Dilley et al, 2008;Washington, 2002;Smith et al, 2006Smith et al, , 2008Smith et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Research has found that students who attended schools with more supportive environment for sexual minorities were significantly less likely to report substance use and emotional distress (Heck et al, 2011(Heck et al, , 2014Konishi et al, 2013). Independent research also note that tobacco industry has historically targeted sexual minority populations (Dilley et al, 2008;Washington, 2002;Smith et al, 2006Smith et al, , 2008Smith et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…There is also evidence that among LGB communities, and especially among lesbian and bisexual women, the marketing efforts of the tobacco industry are more intense and more effective (Dilley et al, 2008;Smith et al, 2006). Much of what is currently known about smoking prevalence among LGB adolescents comes from the United States.…”
Section: Introductionmentioning
confidence: 97%
“…4 Media influence is another prominent explanation: LGB populations report high exposure 5,6 and receptivity 7 to targeted tobacco industry marketing. 8 Tobacco use is also normative in LGB print 9 and entertainment 10 media.…”
Section: Original Investigationmentioning
confidence: 99%
“…34,35 A systematic review of 42 studies on tobacco use among these groups in the US found a significantly higher risk of smoking among sexual and gender minorities compared to the general population (OR = 1.5 to 2.5). 26 In addition to the same risk factors for smoking that confront other groups, sexual and gender minorities also face additional factors that exacerbate their risk, including social environments that are accepting of smoking, 27,36,37 aggressive targeting by the tobacco industry, [38][39][40][41][42] and perhaps most notably stigma-related processes including minority stress, psychological distress, and social isolation. 24,26,[29][30][31]39,[43][44][45][46][47][48][49] The alarmingly high risk of smoking among sexual and gender minorities together with research that has documented a relationship between stigma-related processes and smoking prevalence for these groups raises questions about whether tobacco-related stigma intensifies the disadvantages associated with the stigmas of other social identities.…”
mentioning
confidence: 99%